Appraising Quality of GP Discharge Letters Completed by the Liaison Team for Patients Reviewed by South of Tees Liaison Team - Heba Saeed; Ramanand Badanapuram; Sahana Sridhar; Sagrika Nag (BJPsych Open)
Aims: Discharge letters from liaison services to General Practitioners (GPs) are critical for ensuring continuity of care. These letters should contain essential clinical information that aids GPs in managing patients post-discharge. The purpose of this audit is to assess the quality and completeness of discharge letters from South of Tees liaison services and ensure they meet the necessary standards for effective communication.